Beyond opportunism: Intermediary loyalty in regulation and governance - Kenneth W. Abbott; Philipp Genschel; Duncan Snidal; Bernhard Zangl (Regulation & Governance, 2021)
Regulators and other governors rely on intermediaries to set and implement policies and to regulate targets. Existing literatures focus heavily on intermediaries of a single type – Opportunists, motivated solely by self-interest. But intermediaries can also be motivated by different types of loyalty: to leaders (Vassals), to policies (Zealots), or to institutions (Mandarins). While all three types of loyalists are resistant to the traditional problems of opportunism (slacking and capture), each brings pathologies of its own. We explain the behavioral logic of each type of loyalty and analyze the risks and rewards of different intermediary loyalties – both for governors and for the public interest. We illustrate our claims with examples drawn from many different realms of regulation and governance.
Keywords: 330; delegation; indirect governance; intermediary; intermediary agency